Optimization Of Cooperative Learning Model Number Heads Together To Improve Understanding Of Mathematical Sentence Concepts In Grade IV Elementary School Students - Anand, Talitha Alysia Nasywa (Universitas Nusantara PGRI Kediri, 2025)
This study uses the Classroom Action Research (CAR) method, which is designed to improve the learning outcomes of fourth-grade students by optimizing cooperative learning using the Number Heads Together (NHT) model in mathematics. The study was conducted in two cycles, where each cycle involved the stages of CAR according to Kemmis and McTaggart, namely planning, implementation, observation, and reflection. This study aims to improve the learning outcomes of fourth-grade students in mathematical sentences and calculations through optimizing Cooperative Learning, especially the Number Heads Together model. Data were collected through observation, documentation, interviews, and tests. The results showed that the application of the Number Heads Together model succeeded in significantly improving student learning outcomes from 58.33% in cycle I and achieving a classical learning completion percentage of 83.33% in cycle II. These results confirm that cooperative learning using the Number Heads Together model has great potential in improving the learning outcomes of fourth-grade students in mathematics. This study is expected to produce innovative contributions in improving the quality of mathematics learning, creating an interactive, collaborative, and effective learning environment.